Determinants of Growth in Fast Developing Countries: Evidence from Bundling and Unbundling Institutions - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
Purpose We assess growth determinants in the BRICS (Brazil, Russia, India, China and South Africa) and MINT (Mexico, Indonesia, Nigeria and Turkey) fast-developing nations for the period 2001-2011. Particular emphasis is laid on the bundling and unbundling of ten governance dynamics. Design/methodology/approach- Contemporary and non-contemporary Fixed- and Random-Effects regressions are employed as empirical strategies. GDP growth and real GDP output are used as dependent variables. The governance variables are bundled by means of principal component analysis. Findings- The following are some findings. First, governance is more positively significant in non-contemporary specifications as opposed to contemporary regressions. Second, there is some interesting evidence on the heterogeneity of political governance as a driver. Political governance and its constituents (political stability and voice & accountability) are significantly positive in GDP growth but insignificant in real GDP output regressions. Third, the other governance dynamics are more significant determinants of real GDP output, as opposed to GDP growth. Accordingly, they are insignificant in contemporary regressions and negatively significant in non-contemporary regressions for GDP growth. Fourth, the constituents of economic governance have the highest magnitude in the positive effects of governance dynamics on real GDP output. Practical implications- The following are some practical implications. First, lag determinants are necessary for growth targeting or timing of growth dynamics. Growth drivers for the most part are more significantly determined by past information. Second, political governance is the most important driver of economic growth, with the significance of effects more apparent in non-contemporary regressions. Third, economic governance and institutional governance are more positively predisposed to driving real GDP output than GDP growth. Originality/value- As far as we have reviewed, it is the first study to investigate growth determinants in the BRICS and MINT nations. It has strong implications for other developing countries on the contemporary and non-contemporary dynamics of governance in driving economic prosperity.
Keywords: C52; F21; F23; O40; P37; 330; Economic Growth; emerging countries; governance